Experiences of Special Education Teachers: Difficulties They Face and Solution Suggestions - Epçaçan, Uğur; Bahçeci, Ferhat; Üzüm, Burhan (Mustafa Süleyman ÖZCAN, 2024)
This paper explores special education teachers’ opinions about the reasons for choosing their field, expectations, the problems they face, and their suggestions for these problems. This research was designed according to case study. 34 special education teachers, 13 female and 21 male, in Siirt during the 2022-2023 academic year, participated. The data were analyzed through content analysis. Results reveal that individual and economic factors are effective in choosing the field of special education teachers. The main expectations of teachers were environmental, individual and institutional expectations. Under the environmental expectations category, the highest demand for material support, appropriate educational environment, family education and the profession to be valued was expressed. Under the category of individual expectations, demands such as the need for in-service training, improvement of economic conditions and retirement age were specified. Under the institutional expectations category, the topics of intensive training in undergraduate education and the removal of field changes attracted attention. Environmental, institutional and individual issues categories emerged regarding the problems faced by special education teachers. Under the environmental issues category, the problems of low parent support, deficiencies in materials, lack of knowledge about the field by the society, and seeing teachers as caregivers came to the fore. Under the institutional issues category, problems encountered with school administrations and field changes occurred. In the category of individual issues, problems related to burnout and lacks of in-service training were mentioned.

Bu araştırma özel eğitim öğretmenlerinin alanlarını tercih etme nedenleri, beklentileri, karşılaştıkları sorunlar ve sorunlara ilişkin çözüm önerilerini belirlemeye ilişkin görüşlerini incelemek amacıyla yapılmıştır. Araştırma nitel araştırma yöntemlerinden durum çalışması ile desenlenmiştir. Araştırmaya 2022-2023 eğitim öğretim döneminde Siirt ilinde görev yapan 13’ü kadın 21’i erkek olmak üzere toplam 34 özel eğitim öğretmeni katılmıştır. Araştırma sürecinde ulaşılan veriler içerik analizi ile çözümlenmiştir. Araştırmada özel eğitim öğretmenlerinin alanı seçme konusunda bireysel ve ekonomik faktörlerin etkili olduğu söylenebilir. Öğretmenlerin başlıca beklentileri, çevresel, bireysel ve kurumsal beklentiler şeklinde oluşmuştur. Çevresel beklentiler kategorisi altında en çok materyal desteği, uygun eğitim ortamı, aile eğitimi ve mesleğin değer görmesi talebi dile getirilmiştir. Bireysel beklentiler kategorisi altında hizmet içi eğitim ihtiyacı, ekonomik koşulların iyileştirilmesi ve emeklilik yaşı gibi talepler belirtilmiştir. Kurumsal beklentiler kategorisi altında ise lisans eğitiminde yoğun eğitimlerin verilmesi ve alan değişikliğinin kaldırılması başlıkları dikkat çekmiştir. Özel eğitim öğretmenlerinin alanda karşılaştıkları sorunlara ilişkin çevresel, kurumsal ve bireysel sorunlar kategorileri oluşmuştur. Çevresel sorunlar kategorisi altında veli desteğinin az olması, materyal konusunda eksiklikler yaşanması, toplum tarafından alanla ilgili bilgi eksikliğinin olması ve öğretmenlerin bakıcı olarak görülmesi sorunları ön plana çıkmıştır. Kurumsal sorunlar kategorisi altında okul yönetimleriyle karşılaşılan sorunlar ve alan değişikliği başlıkları oluşmuştur. Bireysel sorunlar kategorisinde ise yıpranma ve hizmet içi eğitim eksikliğine ilişkin sorunlar dile getirilmiştir.
Özel Eğitim Öğretmenlerinin Deneyimleri: Yaşadıkları Zorluklar ve Çözüm Önerileri
Keywords: Other Fields of Education; Alan Eğitimleri